2015
DOI: 10.1177/0194599815582169
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Surgeon Adherence to Pediatric Tonsillectomy Guidelines Regarding Perioperative Dexamethasone and Antibiotic Administration

Abstract: Most hospitals and surgeons administered perioperative dexamethasone routinely. While the overall frequency of antibiotic administration decreased after the guidelines were published, a significant percentage of surgeons continued to give antibiotics routinely, suggesting the need for improved dissemination and implementation of guidelines to promote adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…We identified 46 unique database or registry studies or case series with ≥1000 children (reported in multiple papers) addressing PTH. 3,4,123-176…”
Section: Resultsmentioning
confidence: 99%
“…We identified 46 unique database or registry studies or case series with ≥1000 children (reported in multiple papers) addressing PTH. 3,4,123-176…”
Section: Resultsmentioning
confidence: 99%
“…The first one is that a significant percentage of surgeons in the United States continued to use antibiotics routinely despite the guidelines [ 17 ]. The second issue is a small but considered significant increase in surgery for post-tonsillectomy bleeding following the publication of the guidelines [ 18 ]. The incidence of fever is the only concern in protocols that do not recommend the use of antibiotics, and in such incidences, they do give antibiotic [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…189 In addition, multiple studies have shown no significant change in pain, emergency room encounters, or hospitalization. 29,190-194…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%